Design and simulation of an optimized e-linac based neutron source for BNCT research. (December 2015) - Durisi, E.; Alikaniotis, K.; Borla, O.; Bragato, F.; Costa, M.; Giannini, G.; Monti, V.; Visca, L.; Vivaldo, G.; Zanini, A.
Abstract: The paper is focused on the study of a novel photo-neutron source for BNCT preclinical research based on medical electron Linacs. Previous studies by the authors already demonstrated the possibility to obtain a mixed thermal and epithermal neutron flux of the order of 10 7  cm −2  s −1 . This paper investigates possible Linac's modifications and a new photo-converter design to rise the neutron flux above 5 10 7  cm −2  s −1, also reducing the gamma contamination. Highlights: Proposal of a mixed thermal and epithermal (named hyperthermal) neutron source based on medical high energy electron Linac. Photo-neutron production via Giant Dipole Resonance on high Z materials. MCNP4B-GN simulations to design the photo-converter geometry maximizing the hyperthermal neutron flux and minimizing the fast neutron and gamma contaminations. Hyperthermal neutron field suitable for BNCT preclinical research.